2018
DOI: 10.2215/cjn.12171017
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and Hypertensive Complications of Pregnancy in Women with Nephrolithiasis

Abstract: In women without preexisting diabetes, hypertension, and CKD, a history of nephrolithiasis was associated with gestational diabetes and hypertensive disorders of pregnancy, especially in women with high first trimester body mass index.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 42 publications
(39 reference statements)
1
6
0
Order By: Relevance
“…In the case of instrumental and laboratory studies, against the control group's reference values, at animals of the experimental group there was a hypertension (141/85±5) mm Hg, dyslipidemia (total cholesterol level (5.37±0.33) mmol/L, TG (2.55± 0.24) mmol/L), elevated glucose (8.52±0.17) mmol/L. Some studies have indicated that the most common combination of metabolic syndrome is the combination of obesity, arterial hypertension, hypercholesterolemia and insulin resistance [14,15]. Taking into account the morphometric, instrumental and laboratory parameters of experimental group rats, there are grounds to assert that the used model for introduction into the metabolic syndrome is effective, and females are in a metabolic syndrome.…”
mentioning
confidence: 99%
“…In the case of instrumental and laboratory studies, against the control group's reference values, at animals of the experimental group there was a hypertension (141/85±5) mm Hg, dyslipidemia (total cholesterol level (5.37±0.33) mmol/L, TG (2.55± 0.24) mmol/L), elevated glucose (8.52±0.17) mmol/L. Some studies have indicated that the most common combination of metabolic syndrome is the combination of obesity, arterial hypertension, hypercholesterolemia and insulin resistance [14,15]. Taking into account the morphometric, instrumental and laboratory parameters of experimental group rats, there are grounds to assert that the used model for introduction into the metabolic syndrome is effective, and females are in a metabolic syndrome.…”
mentioning
confidence: 99%
“…Results from our study are consistent with those from a previous follow-up study indicating that the risk of cardiovascular disease associated with GDM was not fully dependent upon the development of type 2 diabetes ( 23 ). In addition, a retrospective cohort study showed that a history of nephrolithiasis was associated with higher risks of GDM [OR (95% CI): 3.1 (1.8–5.3)] and preeclampsia [2.2 (1.3–3.6)], suggesting that stone formation is a marker of metabolic diseases and supporting the link between GDM and kidney stones ( 24 ).…”
Section: Discussionmentioning
confidence: 94%
“…Of note, some studies including the HUNT II study, and a American matched cohort study of 778 women both recently failed to demonstrate an association between CKD and preeclampsia [5,10]. An association between prior history of kidney stones [13] or acute kidney injury that recovers [25] and pregnancy hypertension has also been described, suggesting there may be common maternal factors predisposing to kidney disorders and responses in pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Outcomes for Australian women who had pregnancies while receiving dialysis or after transplantation have previously been explored [7][8][9]. Less is known about the prevalence and impact of earlier stages of chronic kidney impairment [2,10] and transient pathologies such as pyelonephritis and urological disorders [11][12][13]. Our knowledge is also hampered by the lack of routine kidney function testing in pregnancy.…”
Section: Introductionmentioning
confidence: 99%